Introduction to the FreeBSD open-source operating system (LiveLessons (Indianapolis, Ind.), 2015)
"This six-hour video starts with an introduction to the FreeBSD community and explains how it differs from the Linux ecosystem. The video then goes on to provide a firm background in the FreeBSD kernel. The POSIX kernel interfaces are used as examples where they are defined. Where they are not defined, the FreeBSD interfaces are described. The video covers basic kernel services, locking, process structure, scheduling, signal handling, jails, and virtual and physical memory management. The kernel I/O structure is described showing how I/O is multiplexed and the virtual filesystem interface is used to support multiple filesystems. Devices are described showing disk management and their auto-configuration. Next the organization and implementation of the fast filesystem is described, concluding with a discussion of how to maintain consistency in the face of hardware or software failures. The video includes an overview of the ZFS filesystem. The video also covers the socket-based network architecture and layering along with a discussion of routing issues."--Resource description page.